PRO DAN KONTRA PENERAPAN ADOPSI INTERNATIONAL FINANCIAL REPORTING STANDARDS (IFRS) - Ardhiani, Mutiara Rachma; istikhoroh, siti (Fakultas Ekonomi Universitas PGRI Adi Buana, 2018)
A growing world economy makes many new multinationals and cross-country investments, so it requires an accounting standard that can be applied throughout the world. International Financial Reporting Standards (IFRS) are accounting standards that are widely adopted by most countries. IFRS was created as an effort to strengthen the global financial architecture and look for long-term solutions to the lack of transparency in financial information. In addition, with the establishment of the financial statements of IFRS is expected to have good quality information. But in reality, there are two parties with conflicting views regarding the adoption of this standard.